3D Network Structural Poly (Aryl Ether Ketone)-Polybenzimidazole Polymer for High-Temperature Proton Exchange Membrane Fuel Cells - Junqiao Jiang; Erli Qu; Min Xiao; Dongmei Han; Shuanjin Wang; Yuezhong Meng (Advances in Polymer Technology)
Poor mechanical property is a critical problem for phosphoric acid-doped high-temperature proton exchange membranes (HT-PEMs). In order to address this concern, in this work, a 3D network structural poly (aryl ether ketone)-polybenzimidazole (PAEK-cr-PBI) polymer electrolyte membrane was successfully synthesized through crosslinking reaction between poly (aryl ether ketone) with the pendant carboxyl group (PAEK-COOH) and amino-terminated polybenzimidazole (PBI-4NH2). PAEK-COOH with a poly (aryl ether ketone) backbone endows superior thermal, mechanical, and chemical stability, while PBI-4NH2 serves as both a proton conductor and a crosslinker with basic imidazole groups to absorb phosphoric acid. Moreover, the composite membrane of PAEK-cr-PBI blended with linear PBI (PAEK-cr-PBI@PBI) was also prepared. Both membranes with a proper phosphoric acid (PA) uptake exhibit an excellent proton conductivity of around 50 mS cm-1 at 170°C, which is comparable to that of the well-documented PA-doped PBI membrane. Furthermore, the PA-doped PAEK-cr-PBI membrane shows superior mechanical properties of 17 MPa compared with common PA-doped PBI. Based upon these encouraging results, the as-synthesized PAEK-cr-PBI gives a highly practical promise for its application in high-temperature proton exchange membrane fuel cells (HT-PEMFCs).